Elucidating the Molecular Responses to Waterlogging Stress in Cucumis melo by Comparative Transcriptome Profiling - Huanxin Zhang; Guoquan Li; Chengpu Yan; Xinlong Zhang; Na Cao; Meiwang Le; Xinlong Hu; Fanghong Zhu; Wenge Liu (Horticulturae, 2022)
Waterlogging is a serious abiotic stressor that drastically hinders the growth and productivity of melon (Cucumis melo) around the world, due to the reduction in available oxygen levels in the waterlogged tissues. However, the mechanism underlying the responses to waterlogging stress in melon is largely unknown. In this study, physiological and transcriptome data of the waterlogging-sensitive accession ‘L39’ and the waterlogging-tolerant accession ‘L45’ were investigated under conditions of normal water supply and waterlogging stress. The results showed that ‘L45’ exhibited higher chlorophyll contents and lower REL (relative electrolyte leakage) and MDA (malondialdehyde) contents compared with ‘L39’ under waterlogging stress. Additionally, waterlogging stress only led to the stomatal closure and chloroplast damage of ‘L39’. In total, 1748 genes were differentially expressed in the leaves of waterlogging-stressed ‘L45’ compared with control, whereas 3178 genes were differentially expressed in ‘L39’. Further analysis indicated that genes related to chlorophyll synthesis and photosynthesis were more depressed in ‘L39’, while sugar cleavage, glycolysis, and fermentation genes were highly induced in ‘L39’ compared with ‘L45’. The expression of genes involved in ROS (reactive oxygen species) scavenging and hormone signaling significantly differed between ‘L39’ and ‘L45’ in their response to waterlogging stress. Moreover, a total of 311 differentially expressed transcription factors were waterlogging-responsive, among which members of the ERF (ethylene response factor), bHLH (basic helix-loop-helix), and WRKY families might play crucial roles in waterlogging tolerance in melon. This study unraveled the molecular responses to waterlogging stress in melon and could provide helpful candidate genes for further molecular breeding of waterlogging-tolerant melon varieties.